Avaliação do processo de restauração ambiental em uma área de floresta ombrófila mista - Jacomel, Michele Silva Frutuoso (2008)
Nowadays, the State of Paraná has only 1% of Araucaria Forest in conditions of conservation. The restoration of these degraded areas intends to facilitate the succession process and the environmental sustainability of these ecosystems. However, the usual models of ecological restoration are executed by an anthropogenic vision, and their applicability is restrict to high cost of implantation and management. The goal of this study was to evaluate the process of restoration of degraded areas after 30 months of a Revitec® model implantation. The model was installed in a private property at the Piraquara city, Paraná, Brasil. It is compound of diversity islands made by selected vegetal species, implanted in jute bags filled by substratum. The restoration area was divided in two areas, where just one received the restoration model. The evaluate was carried out by biological contents monitoring. The measured phytosociological contents were: absolute frequency, relative frequency, species coverage area, species coverage value in the samples, species relative coverage value. The biometric data showed the quick progress of the implanted species whenever in a presence of a substratum that is rich in organic material and microorganisms. About the plants colonization, a lot of non-implanted species were growing in the area. There were much colonization of Poaceae and Asteraceae species. In the floristic composition of the restoration area, were found 30 species of 17 families, where Asteraceae was the most representative family. The coverage value was different in both areas. In area 1, the major coverage value was Eragrostis airoides Ness (29,75%) and Baccharis dracunculifolia DC (25,50%). In area 2, the specie Andropogon bicornis L. showed 45,75% of relative coverage, following by Baccharis trimera (Less.) DC, with 27,08% of coverage. These species, together, represented 72,83% of total value of the fragment. The diversity of area 2 was 1,32 nats.ind-1. In the area 1, where restoration model was implanted, the diversity was 2,42 nats.ind-1. The visual difference observed between the study areas was proven by the Jaccard index, which value was 32,25%, that demonstrate low similarity between areas. It had an increase of 58% in the number of species in the restored area, which demonstrates the efficiency of the restoration methodology in rescue of local biodiversity. The Revitec® model had success in the reestablishment of vegetation and return of fauna to the restored area.